2020
DOI: 10.1126/sciadv.abc4773
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell analysis of the molecular lineage of chordate embryogenesis

Abstract: Progressive unfolding of gene expression cascades underlies diverse embryonic lineage development. Here, we report a single-cell RNA sequencing analysis of the complete and invariant embryonic cell lineage of the tunicate Ciona savignyi from fertilization to the onset of gastrulation. We reconstructed a developmental landscape of 47 cell types over eight cell cycles in the wild-type embryo and identified eight fate transformations upon fibroblast growth factor (FGF) inhibition. For most FGF-dependent asymmetri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…To assess heterogeneity within clusters or relationships between clusters, similarity metrics or distances can be calculated between the cells [33] and displayed with qualitative or quantitative visuals which preserve these metrics, including hierarchical relationship diagrams such as dendrograms and trees [78, 79], or graph-based network diagrams [80, 81]. Higher-level diagrams that do not seek to display all point-wise information can also be used to represent the results of other inter-cluster analyses [68, 82].…”
Section: Final Thoughts and Discussionmentioning
confidence: 99%
“…To assess heterogeneity within clusters or relationships between clusters, similarity metrics or distances can be calculated between the cells [33] and displayed with qualitative or quantitative visuals which preserve these metrics, including hierarchical relationship diagrams such as dendrograms and trees [78, 79], or graph-based network diagrams [80, 81]. Higher-level diagrams that do not seek to display all point-wise information can also be used to represent the results of other inter-cluster analyses [68, 82].…”
Section: Final Thoughts and Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing data showed that Lefty is normally expressed in the notochord, B-line mesenchyme, and TVC in C. savignyi embryos ( Zhang et al, 2020 ). We detected the expression pattern of Lefty in C. savignyi larvae at different stages by whole-mount in situ hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of marine oganism species reaches about 226,000, occupying a large part in the zoology (Appeltans et al, 2012). Hot research fields, such as evolutionarydevelopmental studies of transitional species and the environmental adaptation studies of organisms, also have urgent needs in single cell sequencing data (Jager and Manuel, 2016;Cao et al, 2019;Schenkelaars et al, 2019;Zhang et al, 2020). As a result, the single-cell studies on marine organisms, focusing on either the cell type recognition or mapping cell lineage and gene regulatory networks, are just unfolding.…”
Section: Future Directions Of Single-cell Sequencing On Marine Organismsmentioning
confidence: 99%
“…As the ocean covers 70% of the earth surface and provides about 90% of the living space on the planet, marine lives are characterized by the incomparable diversity of both species and genes (Poore and Wilson, 1993). Recently, with the rapid development of scRNAseq techniques, single-cell sequencing on marine organisms has promising perspectives,such as the application on studying marine life evolutionalry-development, symbiosis, stem cell and cell regeneration mechanism (Cao et al, 2019;Siebert et al, 2019;Hu et al, 2020;Zhang et al, 2020;Chari et al, 2021;Levy et al, 2021). Here, we review the development of scRNA-seq techniques, the single-cell data analysis methods, and highlight some recent improvements.…”
Section: Introductionmentioning
confidence: 99%